Multi-Colored Light-Emitting Electrochemical Cells Based on Thermal Activated Delayed Fluorescence Host - Jiang Liu (Nature Portfolio, 2017)
Abstract Light-emitting electrochemical cells (LECs) with the thermally activated delayed fluorescence(TADF) host and phosphorescent guests were fabricated using solution process. It is demonstrated for the first time that TADF, a well-known phenomenon that helps to increase electroluminescence efficiency by harvesting excitons from triplet states, is used as a host in LECs. Devices with green, yellow, red and warm white emissions were fabricated, with the best devices showing more than 7000 cd/m2 stable emission and a peak efficiency over 7 cd/A. Under high voltage stress, a burst of extremely high luminance of over 30,000 cd/m2 was observed. All these LEC devices are extremely simple with only one active layer. Thus, our results could pave way to produce low- cost light source with high luminance, using TADF molecules.